Cognitive Strategies and Textual Genres in the Teaching and Evaluation of Advanced Reading Comprehension (ARC) - García-Sánchez, Jesús-Nicasio; García-Martín, Judit (Frontiers in Psychology, 2021)
In the last decade, published data on the performance of Latin American students have concerned educators and researchers, making critical reading or advanced reading comprehension, one of the priorities of Higher education. That is why this article presents the results of a study carried out in a Latin American university in which the perceptions of students and professors are analysed regarding the strategies and textual genres used to work and cross-evaluate the advanced reading comprehension (ARC). This study is materialized in the application of an ad hoc online questionnaire, in its two versions (students and teachers), designed through SurveyMonkey. For this, it has the participation of 182 teachers and 2,775 students. The validation of the implemented instruments is provided, starting from an EFA and providing a CFA. There are several trends in the use of specific textual strategies and typologies to work and evaluate ARC, by both, depending on the department of assignment. The evidence found is provided and evaluated considering the implications for literacy across curriculum instruction and assessment in higher education in Latin America, including study limitations and prospects for overcoming them.